Haptenation of Macrophage Migration Inhibitory Factor: A Potential Biomarker for Contact Hypersensitivity - Ndreu, Lorena; Sasse, Samantha; Karlberg, Ann-Therese; Karlsson, Isabella (Frontiers in Toxicology, 2022)
The immunological response in contact hypersensitivity is incited by small electrophilic compounds, known as haptens, that react with endogenous proteins after skin absorption. However, the identity of hapten-modified proteins seen as immunogenic remains as yet largely unknown. We have, in a recent study, identified for the first time a hapten-modified protein in vivo, in the local lymph nodes of topically treated mice with the model hapten tetramethylrhodamine isothiocyanate (TRITC). The TRITC modification was located on the N-terminal proline of the protein macrophage migration inhibitory factor (MIF). The focus of the current study was to investigate the presence of the same hapten-protein conjugate in blood samples from the mice treated topically with TRITC. Furthermore, TRITC modifications of the two major blood proteins, namely hemoglobin (Hb) and albumin (Alb), as well as TRITC modifications of MIF other than the N-terminal proline, were examined. Following incubation with different molar ratios of TRITC, a proteomic approach was applied to characterize conjugate formation of the three aforementioned proteins, using high resolution mass spectrometry (HRMS). The targeted screening of the TRITC-treated mice blood and lymph node samples for these sites led to the identification of only the same TRITC-MIF conjugate previously detected in the lymph nodes. No Hb and Alb conjugates were detected. Quantification of both the TRITC-modified and unmodified N-terminal peptide of MIF in blood and lymph node samples gave interesting insights of MIF’s role in murine contact hypersensitivity. Incubation of MIF with four different haptens encompassing different reactivity mechanisms and potencies, showed adduct formation at different amino acid residues, suggesting that MIF can be the preferred target for a wide variety of haptens. The present study provides essential progress toward understanding of hapten-protein conjugate formation in contact hypersensitivity and identifies hapten-modified MIF as a potential biomarker for this condition. Further investigation of MIF as a target protein for other haptens can be a next step to investigate if MIF is a biomarker that can be used to develop better diagnostic tools and targeted therapeutics for individuals with allergic contact dermatitis.